Pengembangan Sistem Ketahanan Pangan dalam Kerangka Penghapusan Kemiskinan - Mafruhah, Izza - (Jurnal Ilmu Ekonomi dan Pembangunan, 2009)
Food security is created when we consider the four food security subsystems. Subsystem includes the production, import-export subsystem, subsystem distribution, and consumption subsystems. Food policy must be viewed holistically four subsystems. The subsystem development can not be done partially, a system will work well if all the elements in the system is working properly. Irregularities one element or subsystem will cause the fragility of the system, which in turn led to the collapse of the system as a whole.